Applications of Symmetry Methods to Partial Differential Equations - Bluman, George W.; Cheviakov, Alexei F.; Anco, Stephen C.; SpringerLink (Online service) (New York, NY : Springer New York, 2010)
This is an accessible book on advanced symmetry methods for partial differential equations. Topics include conservation laws, local symmetries, higher-order symmetries, contact transformations, delete "adjoint symmetries," Noether$1 (Bs theorem, local mappings, nonlocally related PDE systems, potential symmetries, nonlocal symmetries, nonlocal conservation laws, nonlocal mappings, and the nonclassical method. Graduate students and researchers in mathematics, physics, and engineering will find this book useful. This book is a sequel to Symmetry and Integration Methods for Differential Equations (2002) by George W. Bluman and Stephen C. Anco. The emphasis in the present book is on how to find systematically symmetries (local and nonlocal) and conservation laws (local and nonlocal) of a given PDE system and how to use systematically symmetries and conservation laws for related applications.s
Local Transformations and Conservation Laws -- Construction of Mappings Relating Differential Equations -- Nonlocally Related PDE Systems -- Applications of Nonlocally Related PDE Systems -- Further Applications of Symmetry Methods: Miscellaneous Extensions.
Keywords: Mathematics; Topological Groups; Global analysis (Mathematics).; Mathematics; Topological Groups, Lie Groups; Analysis